P40 COVID 19: A NEW RISK FACTOR IN CARDIAC SURGERY?. (18th May 2022) - Santise, G; Mariniello, A; Desoky, A; Nardella, S; Franciulli, M; Iavazzo, A; Maselli, D
Abstract: Introduction: Since the beginning of the actual pandemia, several patients with positive anamnesis for Covid 19, are undergoing a cardiac operation. Aim of the study is to analize if the Covid 19 past infection may impact on cardiac surgery outcome. Method: All the patients with a history of Covid 19 positivity, who underwent a cardiac operation at the Clinica Mediterranea in Naples from the 1st of february 2021 to the 31st dicember 2021, have been included in the study. For those patients we evaluated the basal respiratory condition, with a chest Xray or CT scan, a pneumology consult and a spirometry if required. Postoperative outcome has been evaluated analizing ventilation time, intensive care and postoperative lenght of stay, acute renal failure, acute espiratory failure, postoperative complications and death. Results: Thirtheen patients on 358 had a positive anamnesis for Covid19, but a negative swab at the admission. The mean time from the infection has been 5.1 +/– months, 5 patients have had poor or no symptoms, while the remnants moderate or sever ones with evidence of interstitial pneumonia, one patient had developed extrapulmonary complications (valvular thrombosis).